Construction géohistorique du « sauvage » de la Garonne toulousaine : quelle part de naturalité dans les paysages fluviaux ? (2ème partie) - Philippe Valette; Jean-Michel Carozza; Denis Salles; Mélodie David; Guillaume Simonet (Développement Durable et Territoires)
The Garonne between Toulouse and the confluence of the Tarn is composed of many wetlands. Here, various protective devices would label a "wild" dimension to the river, supporting its maintenance and conservation without actually questioning their original condition. Given this situation, how to consider the part of naturalness of river landscapes of the Garonne today? According to managers, the Garonne has a strong image of "wild" river while geohistorical heritage rather shows Garonne impacted by human activities. This work explores the meaning of the gap between the reality and geohistorical conveyed by contemporary representations of the river picture.